Overhead Allocation with Imperfect Markets and Nonlinear Technology. - Kaplan, Robert S.; Welam, Ulf Peter (The Accounting Review, 1974)
This article presents a study on the overhead allocation with imperfect markets and nonlinear technology in accounting in the U.S. The overhead costs generated by the traditional historical-cost-based accounting system are used for pricing usage of scarce resources. These costs must be below or at most equal to the marginal value of such resources as determined by the dual variables of the programming model. It is natural to object to the proposed method since we have a specific management decision model which generates valuations for scarce resources.